2021
DOI: 10.1007/s10964-021-01426-y
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and the Development of Depressive Symptoms in Adolescence: The Role of Regulating Positive and Negative Affect

Abstract: Although widely accepted, attachment theory’s hypothesis that insecure attachment is associated with the development of depressive symptoms through emotion regulation strategies has never been longitudinally tested in adolescence. Additionally, previous research only focused on strategies for regulating negative affect, whereas strategies for regulating positive affect may also serve as a mechanism linking insecure attachment to depressive symptoms. This study aimed to fill these research gaps by testing wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
11
0
5
Order By: Relevance
“…Trait attachment is generally considered a relevant factor for child psychological problems [1]. Specifically, children who are less securely attached at a trait level are more vulnerable to develop psychological problems when experiencing stress, underlain by several mechanisms [12], among which are decreased support-seeking [13] and the use of less adaptive emotion regulation strategies [14]. Interestingly, attachment theory does suggest that there is room for change and trait attachment can be updated in response to changes in the interpersonal environment ('lawful change') [15,16].…”
Section: Trait and State Attachmentmentioning
confidence: 99%
“…Trait attachment is generally considered a relevant factor for child psychological problems [1]. Specifically, children who are less securely attached at a trait level are more vulnerable to develop psychological problems when experiencing stress, underlain by several mechanisms [12], among which are decreased support-seeking [13] and the use of less adaptive emotion regulation strategies [14]. Interestingly, attachment theory does suggest that there is room for change and trait attachment can be updated in response to changes in the interpersonal environment ('lawful change') [15,16].…”
Section: Trait and State Attachmentmentioning
confidence: 99%
“…Insecure attachment is associated with psychological problems, in particular with internalizing symptoms (e.g., depressive symptoms) in children and adolescents [ 36 , 37 , 38 , 39 ]. A recent meta-analysis revealed an overall moderate effect size (r = 0.31) for the association between attachment and depression [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal data on the association between attachment and depressive symptoms through emotion regulation are rare. Verhees et al [ 38 ] showed that an insecure attachment style was associated with the development of more depressive symptoms, mediated by brooding on negative emotions and a dampening of positive affect in case of anxious attachment style, whereas a reduced focus on positive affect mediated the link between avoidant attachment style and depressive symptoms. Therefore, it is important to investigate emotion regulation, especially sadness regulation, as a possible mediator of the relationship between attachment and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kerns and Brumariu (2014) discussed insecure and disorganized attachment as risk factors for the development of affective disorders and that this association might trace back, in part, to less competent emotion regulation capacities in insecurely attached children. A hypotheses that was recently supported by Verhees et al (2021) , who found a mediation pathway between attachment insecurity, the regulation of positive, as well as negative affect and the development of depressive symptoms in a large longitudinal sample of adolescents.…”
Section: Introductionmentioning
confidence: 81%
“…Thus, our findings highlight the importance of specific micro-interactional patterns of mother–child interaction for infants’ regulation ( Müller et al, 2015 ) and the development of a secure attachment quality. Consequently, the interactive dysregulation could be partly responsible for the increased risk of developing mental disorders later in life (compare Verhees et al, 2021 ). Nevertheless, child emotion regulation and their later psychopathological development was not assessed in the current study.…”
Section: Discussionmentioning
confidence: 99%